The Influence of Profitability on Firm Value with ESG Disclosure as a Moderating Variable - Ardhea Kirana Putri Riwanda; Neni Maryani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates how a company’s profitability influences its firm value, while considering Environmental, Social, and Governance (ESG) disclosure as a moderating factor. Previous studies show inconsistent results regarding the profitability–firm value relationship, and limited research has explored the moderating role of ESG disclosure in the Indonesian context. Therefore, this study aims to examine whether profitability affects firm value and whether ESG disclosure strengthens this relationship. The research focuses on firms listed on the Indonesia Stock Exchange (IDX) during 2018–2024. Using a quantitative causal design, secondary data were collected from annual and sustainability reports of 273 data and analyzed using Moderated Regression Analysis (MRA). The findings indicate that higher profitability significantly enhances firm value, suggesting that financially strong firms are more attractive to investors. Moreover, ESG disclosure strengthens this relationship, implying that transparent and responsible sustainability reporting increases investor confidence and market valuation. These results support signaling theory, which posits that profitability and ESG disclosure act as credible signals of firm quality to the market. Overall, the study highlights the strategic importance of integrating financial and sustainability performance to create long-term corporate value.